FROM HR STRATEGY TO HR PERFORMANCE IN RURAL BANKING - Muafi Muafi (Jurnal Keuangan dan Perbankan, 2014)
This research used 194 HR managers from rural banks in Daerah Istimewa Yogyakarta and Central Java,Indonesia as the samples and used purposive sampling technique. The examining of the configuration andcontingency approach included regression euclidience distance. The result of the configuration and contingencyapproach explained that there was misalignment between HR strategy and contingency variable such asexternal environmental. However, if it was analyzed deeply, this condition also emerged the traditionalstrategy and innovative strategy. In other contingency variables such as training model, there was an alignmentof HR strategy, either traditional HR strategy or innovative HR strategy.